Trooping to the supermarket exploring behaviors of 3-4 year olds in a public setting - Bailey, R. R. (2003)
Twenty one children ages 3-4 years old enrolled at the Day Care Laboratory of UPLB were taken to a community field trip in an attempt to observe acceptable behaviors in a public place last January 19, 2012. The kids in class were made to pretend that were made to pretend that they were picking items from grocery shelves and queuing up at the cashier. Seventeen out of the 21 children were reported to be excited, anticipating and unusually bubbly or talkative before the trip. Three were observed to have no change in behavior and one child was found to be unusually difficult on the day of the trip. Although nine of the children were wandering to other sections on their own, 19 described to manifested politely request to buy a familiar or preferred item/brand. No child manifested complaining, whining, and crying. Only one child was observed to sit on the floor when not allowed to go to be a particular section. However, no child was reported to throw a tantrum during the visit. Children were also found to pick on items, especially snack items that were familiar to them. They were also observed to prefer throughout the grocery trip and this may be attributed to the presence of their classmates and teachers. Overall, they were found to display acceptable behaviors for 3-4 year old inside a grocery.
Keywords: Behavioral assessment of children; Supermarkets